THERMAL NEUTRON FLUX MAPPING ON A TARGET CAPSULE AT RABBIT FACILITY OF RSG-GAS REACTOR FOR USE IN k0-INAA - Sutisna (Jurnal Teknologi Reaktor Nuklir Tri Dasa Mega, 2015)
Instrumental neutron activation analysis based on the k0 method (k0-INAA) requires the availability of the accurate reactor parameter data, in particular a thermal neutron flux that interact with a targets inside the target capsule. This research aims to determine and map the thermal neutron flux inside the capsule and irradiation channels used for the elemental quantification using the k0-AANI. Mapping of the thermal neutron flux (фth) on two type of irradiation capsule have been done for RS01 and RS02 facilities of RSG-GAS reactor. Thermal neutron flux determined using Al-0,1%Au alloy through 197Au(n,g) 198Au nuclear reaction, while the flux mapping done using statistics R. Thermal neutron flux are calculated using k0-IAEA software provided by IAEA. The results showed the average thermal neutron flux is (5.6±0.3)×10+13 n.cm-2.s-1; (5.6±0.4)×10+13 n.cm-2.s-1; (5.2±0.4)×10+13 n.cm-2.s-1 and (5.3±0.4)×10+13 n.cm-2.s-1 for Polyethylene capsule of 1st , 2nd, 3rd and 4th layer respectively. In the case of Aluminum capsule, the thermal neutron flux was lower compared to that on Polyethylene capsule. There were (3.0±0.2)×10+13 n.cm-2.s-1; (2.8±0.1)×10+13 n.cm-2.s-1; (3.2±0.3)×10+13 n.cm-2.s-1 for 1st, 2nd and 3rd layers respectively. For each layer in the capsule, the thermal neutron flux is not uniform and it was no degradation flux in the axial direction, both for polyethylene and aluminum capsules. Contour map of eight layer on polyethylene capsule and six layers on aluminum capsule for RS01 and RS02 irradiation channels had a similar pattern with a small diversity for all type of the irradiation capsule.